1995
DOI: 10.1111/j.1574-6968.1995.tb07543.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma gallisepticum16S rRNA genes

Abstract: The genome of Mycoplasma gallisepticum A5969 contains a truncated pseudogene for 16S rRNA in addition to a single unsplit rRNA-operon and a second discontinuous set of rRNA genes. Other M. gallisepticum strains tested do not possess the truncated gene. This gene is almost identical to full-size isolated 16S rRNA gene starting from at least 500 nucleotides upstream of the coding sequence and ending at the 977th nucleotide within the structural part of 16S rRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Since the 16S rRNA gene is a highly conserved gene and ubiquitous in bacteria and archae, the similarity in this region is high with less variation. Previous research has used this gene region to identify a wide diversity of microbes within a single sample and single workflow and identification of taxa present in the sample [ 26 , 27 , 30 , 31 ]. This study observed an evolutionary relationship among all isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 16S rRNA gene is a highly conserved gene and ubiquitous in bacteria and archae, the similarity in this region is high with less variation. Previous research has used this gene region to identify a wide diversity of microbes within a single sample and single workflow and identification of taxa present in the sample [ 26 , 27 , 30 , 31 ]. This study observed an evolutionary relationship among all isolates.…”
Section: Discussionmentioning
confidence: 99%
“…many biases have to be evaluated when genome copies are employed, as biological features of mycoplasma strain, phase of mycoplasma growth, growth conditions and mycoplasma sample handling after the cultivation 8 . Besides, the copy number of the 16s rRnA gene differs among the different species of mycoplasma, introducing as such a further bias to the genome copy number evaluation 39,40 . Additionally, the yield provided by the different DnA isolation methods may vary widely, generating outputs that do not correlate to the real bacterial amounts in the samples, if the DnA isolation method is changed.…”
Section: /13mentioning
confidence: 99%